De-Europeanisation of Civil Society and Public Debates in Turkey: The Kurdish Question Revisited. Issue 1 (2nd January 2016) - Kaliber, Alper
Abstract: This study discusses the dynamics of de-Europeanisation and the changing impact of Europe on the politically mobilised civil society involved in the public debates concerning Turkey's Kurdish question. The article first critically assesses how and in what ways the legal and constitutional reforms on the freedom of assembly required by the European Union (EU) changed the political structure in which civil society organisations (CSOs) operate in Turkey. It then examines the views of CSOs on the potential roles and limitations of the EU in the Kurdish question and the peace process which lasted between March 2013 and July 2015. It also delineates the reasons why the political context of Europeanisation is not seen as instrumental by these CSOs to framing and justifying their arguments.